2019
DOI: 10.3892/ol.2019.10696
|View full text |Cite
|
Sign up to set email alerts
|

The CK2 inhibitor CX4945 reverses cisplatin resistance in the A549/DDP human lung adenocarcinoma cell line

Abstract: Lung cancer negatively impacts global health, and the incidence of non-small cell lung cancer (NSCLC) is highest among all forms of lung cancer. Chemotherapy failure mainly occurs due to drug resistance; however, the associated molecular mechanism remains unclear. Casein kinase II (CK2), which plays important roles in the occurrence, development and metastasis of many tumours, regulates Wnt signaling by modulating β-catenin expression. In the present study the effects of the CK2 inhibitor, CX4945 on cisplatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…When Table 1 is examined, it is seen that IC50 values for CDDP ranged from 2.06 to 9.14 µM in cancer cell lines. Consistent with these results, it is reported that the IC50 values of CDDP on HeLa and A549 cell lines vary between 0.75 to 8.6 µM (Gumus et al, 2009;Casagrande et al, 2013;Singh et al, 2015) and 1.12 to 7 µM (Adach et al, 2016;Jin et al, 2019;Zhang et al, 2020), respectively. Similarly, it is reported that the IC50 values of CDDP on MCF-7 and HepG2 cell lines vary between 3.09 to 12.5 µM (Aung et al, 2007;Gumus et al, 2009;Mansouri-Torshizi et al, 2016) and 7.75 to 24.1 µM (Sakinah et al, 2007;Adach et al, 2016;Hashiesh et al, 2018), respectively.…”
Section: Resultssupporting
confidence: 64%
“…When Table 1 is examined, it is seen that IC50 values for CDDP ranged from 2.06 to 9.14 µM in cancer cell lines. Consistent with these results, it is reported that the IC50 values of CDDP on HeLa and A549 cell lines vary between 0.75 to 8.6 µM (Gumus et al, 2009;Casagrande et al, 2013;Singh et al, 2015) and 1.12 to 7 µM (Adach et al, 2016;Jin et al, 2019;Zhang et al, 2020), respectively. Similarly, it is reported that the IC50 values of CDDP on MCF-7 and HepG2 cell lines vary between 3.09 to 12.5 µM (Aung et al, 2007;Gumus et al, 2009;Mansouri-Torshizi et al, 2016) and 7.75 to 24.1 µM (Sakinah et al, 2007;Adach et al, 2016;Hashiesh et al, 2018), respectively.…”
Section: Resultssupporting
confidence: 64%
“…Therefore, down-phosphorylation of these candidate substrates could modulate the Wnt signaling pathway. Supporting this hypothesis, previous studies highlights that CK2 is a positive regulator of Wnt signaling pathway and CK2 inhibition by CX-4945 has been associated with Wnt/β-catenin inhibition [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 83%
“…We have previously shown in prostate cancer that CK2 inhibition has a negative impact on mitochondrial health through decreased membrane potential and Ca 2+ flux [ 27 , 46 ]. CK2 has significant influence on numerous DNA repair and other pathways activated by radiation and cisplatin [ 27 , 47 , 48 , 49 ]; loss of CK2 improves sensitivity to cisplatin or radiation in numerous cancers, including head and neck cancer [ 42 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. CX-4945 blocks DNA repair after cisplatin or gemcitabine treatment [ 51 , 63 ], and next generation platinum Pt(IV) prodrugs conjugated with CX-4945 have shown efficacy in other cancer types [ 64 ].…”
Section: Discussionmentioning
confidence: 99%